The Effect of Work-Life Balance and Work Engagement on Employee Performance: A Literatur Review - Maghfiratika, Tishar; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
Work-life balance and work engagement are key factors influencing employee performance in workplace settings. In the current highly competitive environment, companies need to enhance productivity and operational efficiency. Workers who effectively manage their work and personal lives often experience reduced stress and improved performance results. This equilibrium enhances job satisfaction while also bolstering employee loyalty, thereby boosting overall organizational efficiency. Moreover, individuals who are deeply involved in their work frequently attain remarkable outcomes as they tackle their responsibilities with heightened enthusiasm and responsibility. Still, numerous organizations struggle to establish an environment that fosters both work-life balance and employee involvement. The study titled "The Effect of Work-Life Balance and Work Engagement on Employee Performance" seeks to examine the connection among work-life balance, work engagement, and employee performance. This qualitative study employs library survey techniques and descriptive analytical methods to elucidate events that have happened recently or historically. The findings suggest that the connection between work-life balance and work engagement can significantly enhance employee performance. However, several studies indicate that while job engagement greatly affects performance, the effect of work-life balance might not be as clear.